2021
DOI: 10.33087/jiubj.v21i1.1043
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Daya Tampung Jaringan Jalan Tidak Sebidang (Studi Kasus: Flyover Teuku Umar, Kota Bandar Lampung)

Abstract: The city of Bandar Lampung as the capital of Lampung Province causes a high number of movements so that traffic jams cannot be avoided on several roads in the City of Bandar Lampung. Responding to these problems, the city government of Bandar Lampung has carried out many flyovers as an effort to increase road capacity to meet high demand and is projected to continue to increase. The Teuku Umar flyover in Kedaton sub-district is one of the three flyovers built in 2017-2018. Jalan Teuku Umar has quite a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In Indonesia, for example, the solution of short double-decker road sections, i.e. flyovers is common (Saraswati and Gunari, 2021). Some other transportation scholars even suggested that a road can be called highway just if all of its junctions have flyovers on top of them (van Nes, 2021).…”
Section: High Occupancy Vehicle Lanesmentioning
confidence: 99%
“…In Indonesia, for example, the solution of short double-decker road sections, i.e. flyovers is common (Saraswati and Gunari, 2021). Some other transportation scholars even suggested that a road can be called highway just if all of its junctions have flyovers on top of them (van Nes, 2021).…”
Section: High Occupancy Vehicle Lanesmentioning
confidence: 99%
“…Kota Bandar Lampung berpenduduk 1 184 949 juta jiwa pada tahun 2021 dan mencapai 1 209 937 juta jiwa pada tahun 2022 [2]. Perkembangan Kota Bandar Lampung yang tinggi menyebabkan jumlah pergerakannya tinggi pula [3].…”
Section: Pendahuluanunclassified